15.0k views
1 vote
The functions fand g are defined as follows:

f(x) = -5x-1

g(x) = 2x + 2

Find f(3) and g(-4).

Simplify your answers as much as possible.

f(3) =

g(-4) = ​

The functions fand g are defined as follows: f(x) = -5x-1 g(x) = 2x + 2 Find f(3) and-example-1
User Ray Perea
by
5.7k points

1 Answer

5 votes

Explanation:

Given

f(x) = -5x - 1

and

g(x) = 2x + 2

Now

f(3) = - 5 * 3 - 1

= -15 -1

= -16

Also

g(-4) = 2 * (-4) + 2

= - 8 + 2

= - 6

User Phillbaker
by
6.0k points